DNA and biotechnology - Fitzgerald-Hayes, Molly; Fitzgerald-Hayes, Molly; Frieda, Reichsman (Amsterdam, Elsevier, 2010)
Appropriate for a wide range of disciplines, from biology to non-biology, law and nursing majors, DNA and Biotechnology uses a straightforward and comprehensive writing style that gives the educated layperson a survey of DNA by presenting a brief history of genetics, a clear outline of techniques that are in use, and highlights of breakthroughs in hot topic scientific discoveries.
Includes bibliographical references.; Glossary 369-380p.; Index 381-389p.